Research progress on small extracellular vesicles in diabetic nephropathy - Bingqing Yu; Bingqing Yu; Lanfeng Wang; Yiping Mao; Yiping Mao; Xinyi Hu; Xinyi Hu; Yukang Lu; Yukang Lu; Jiahui He; Jiahui He; Xiaoying Yuan; et al. (Frontiers in Cell and Developmental Biology)
Virtually all cell types are capable of secreting small extracellular vesicles (sEV), which can be internalized by recipient cells, thereby serving as vehicles for intercellular communication. The cargoes of these vesicles, such as microRNAs, circular RNAs, proteins, and lipids, play significant roles in both normal cellular functions and the pathogenesis of various diseases. Diabetic Nephropathy (DN), a complication arising from diabetes, is expected to contribute to a 54% increase in the global diabetic population between 2015 and 2030, leading to substantial economic burdens on individuals and healthcare systems. sEVs, as promising biomarkers, demonstrate diverse mechanistic responses in different types of Diabetic Kidney Disease (DKD). They also hold advantages in the early prediction of renal damage. This article reviews the functional mechanisms of sEVs in DKD and their potential as therapeutic targets and biomarkers.